2014
DOI: 10.1590/1678-4499.0075
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização genética de uma coleção de germoplasma de cagaiteira, uma espécie nativa do cerrado

Abstract: Cagaiteira is a common fruit species in the Cerrado. The plant produces a berry fruit that is consumed fresh or processed in several ways. Concerning the yield potential of the species, there is interest in its domestication for large-scale production. To this aim, the evaluation of genetic variability is essential to support breeding and domestication programs for the species. In this context, this study aimed to estimate genetic parameters of quantitative traits of the germplasm collection of Eugenia dysente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…O fruto apresenta formato oval, achatado ou elipsoide, com massa de 14 a 20 gramas, sendo o epicarpo membranoso e de brilho intenso, e o mesocarpo e o endocarpo, carnosos (Silva et al, 2015a(Silva et al, , 2015bSilva, 2016). A frutificação da cagaita ocorre aproximadamente um mês depois do florescimento (de agosto a setembro) (Almeida Júnior et al, 2014). É um fruto com teor significativo de fibras alimentares, vitaminas, minerais e baixo valor energético (cerca de 20 a 29 kcal em 100 gramas).…”
Section: Cagaitaunclassified
See 1 more Smart Citation
“…O fruto apresenta formato oval, achatado ou elipsoide, com massa de 14 a 20 gramas, sendo o epicarpo membranoso e de brilho intenso, e o mesocarpo e o endocarpo, carnosos (Silva et al, 2015a(Silva et al, , 2015bSilva, 2016). A frutificação da cagaita ocorre aproximadamente um mês depois do florescimento (de agosto a setembro) (Almeida Júnior et al, 2014). É um fruto com teor significativo de fibras alimentares, vitaminas, minerais e baixo valor energético (cerca de 20 a 29 kcal em 100 gramas).…”
Section: Cagaitaunclassified
“…A temperatura varia entre 22 °C e 27 °C, e a umidade relativa do ar alcança taxas entre 38 e 40% no inverno seco, enquanto no período chuvoso, a umidade é elevada, atingindo 97%. A vegetação do bioma é caracterizada como aberta ou floresta semidecidual, possui habitats xerofíticos, mésicos e enclaves com regiões úmidas, caracterizada por árvores de médio porte, galhos e troncos retorcidos, raízes densas e acomodadas a uma menor pluviosidade (Conceição, 2012;Mendes et al, 2012;Almeida Júnior et al, 2014).…”
unclassified
“…Four other phenotypes could be selected for their high content of vitamin C: numbers 4, 14, 29 (belonging to cluster 1) and number 60 (cluster 2); however, their fruit weight and pulp yield were outside the required parameters (Table S2). Therefore, together with the analysis of the performance of the phenotypes, studies on genetic divergence are of great importance for breeding programs because they assess the variability among phenotypes [37] and provide information for the identification of mother plants that can be used in crosses with a higher probability of obtaining superior progeny in the segregating generations [42,71]. However, it is not possible to capture the combining ability among parents based solely on their individual performance.…”
Section: Classification Of Acerola Phenotypesmentioning
confidence: 99%
“…No studies have reported the biochemical and morphological characterization of acerola phenotypes for the region of Western Paraná, where the commercial production of acerola is expanding in Brazil. In this context, to assess the variability in fruit quality among different individuals of acerola, it is of great importance to start breeding programs [35][36][37]. In particular, pre-screening within intraspecific phenotypes allows large amounts of acerola germplasm to be screened at a relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, there is a risk of definitive loss of genetic material present in the remnants, which justifies studies of natural variability as a basis for conservation and breeding strategies. Studies with fruit species from the Cerrado have shown high genetic variability with structuring among populations, which can be used as support in actions of collection, management and exploitation of genetic resources (Diniz-Filho et al 2009, Ganga et al 2009, Moura et al 2013, Almeida Junior et al 2014, Collevatti et al 2018, Almeida et al 2019.…”
Section: Introductionmentioning
confidence: 99%